Synthesis, Characterization, and Preliminary Evaluation of Antimicrobial activity of Imines derived from Vanillic Acid Conjugated to Heterocyclic - Sabzi, Noor Ali; Mohammed Jawad , May (Iraqi Journal of Pharmaceutical Sciences, 2023)
The purpose of this research is to prepare new vanillic acid derivatives with 1,2,4-triazole-3-thiol heterocyclic ring and evaluate their antimicrobial activity in a preliminary assessment. A multistep synthesis was established for the preparation of new vanillic acid-triazole conjugates. The intermediate of 4-(4-amino-5-mercapto-4H-1,2,4-triazol-3-yl)-2-methoxyphenol (4) reacts with different heterocyclic aldehydes (thiophene-2-carboxaldehyde, pyrrole-2-carboxaldehyde, thiophene-3-carboxaldehyde, and furfural ) in ethanol containing few drops of acetic acid yielded the corresponding 4-(4-(substituted amino)-5-mercapto-4H-1,2,4-1triazol-3-yl)-2-methoxy phenol derivatives (5-8). These compounds were characterized spectroscopically by FT-1IR and 1H-1NMR. These imine derivatives (5-8) were tested for their antimicrobial activity and compared with three different standard references (amoxicillin, ciprofloxacin, and fluconazole). Overall, compounds 6 and 8 exhibited varying degrees of inhibitory effects on the growth of the examined bacterial species and fungus. The most active one is compound 6 having pyrrole ring imine derivative showed potent activity against C. 1albicans and moderate activity against all tested bacteria compared to other derivatives but no activity toward P. 1aeruginosa and P. 1mirabilis.